Camera color vision for crop ripeness model. - Wan Ismail, Wan Ishak; Mohd Kassim, Muhamad Saufi; Razali, Mohd. Hudzari (2013)
Color is the main indicator used to recognize ripeness of the agricultural products and thus determine the best time to harvest the products. In this research, a Nikon coolpix 4500 digital camera (Nikon, Japan) was used to investigate the relationship between oil content in oil palm fruit and its surface color distribution. The relationship of between oil content with optical properties for fruit color of hue was illustrated using trend line analysis of polynomial second order method. The results showed that the hue value of FFB image was highly significant in determining the oil content of oil palm fruit: